PONDOK PESANTREN DITINJAU DARI PERATURAN DAERAH NOMOR 2 TAHUN 2014 TENTANG PENYELENGGARAAN PENDIDIKAN DAN KEBUDAYAAN DAERAH DI SULAWESI TENGAH - Besse Tenriabeng Mursyid (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2021)
One way to educate the nation's life is through education. This is in line with the 1945 Constitution Article 31 paragraph (1) which states that "every citizen has the right to education". One of the educational institutions that has an important role in the development of this religious character is pesantren. Islamic boarding school education can be organized by the Government and/or community groups of religious adherents whose function is to prepare students to become members of the community who understand and practice the values ​​of their religious teachings and/or become experts in religious knowledge. Pesantren education can be held in formal, non-formal, and informal education channels. As an educational institution, Islamic boarding schools have made a major contribution to the formation of religious Indonesian people. Therefore, it is necessary to strengthen this pesantren-based learning in Indonesian Islamic society. Several constitutional facts which state that the 20% allocation for education is important to note. In empirical facts, the expectations of Article 31 paragraph (4) of the Constitution are not immediately realized properly, because the existence of Islamic boarding schools and religious education is not included in the allocation. the budget allocation. The presence of regulations cannot be denied is something very important, as a follow-up to the existence of Law Number 20 of 2003 concerning the National Education System by the regional government of Central Sulawesi Province, an academic document and regional regulation Number 2 of 2014 concerning the implementation of Regional Education and Culture were issued. , specifically described in the weighing sheet of regional regulations, it is explained that the people of Central Sulawesi Province have a diversity of cultures, ethnicities, races, religions and regional origins, which have the potential to create social problems so that regional policies in the field of education and culture are needed that can strengthen a sense of unity and a sense of nationality. This is a breath of fresh air when viewed from the perspective of the existence of these regional regulations that will touch all educational institutions, but in fact this is not the case. However, in 2019 there was Law Number 18 of 2019 concerning Islamic Boarding Schools which became a breath of fresh air for Islamic Boarding School educational institutions in all regions in the unitary territory of the Republic of Indonesia.